An Overview of Global Observing Systems Relevant to GODAE - Mike Johnson; Maria Hood; David Meldrum; Chris Sabine; Robert Weller; Uwe Send; Dean Roemmich; Mark Merrifield; D.E .Harrison; Gustavo Goni; Graeme Ball; Candyce Clark; et al. (Oceanography, 2009)
A global ocean observing system for the physical climate system, comprising both in situ and satellite components, was conceived largely at the Ocean Observations conference in St. Raphael, France, in October 1999. It was recognized that adequate information was not available on the state of the world ocean or its regional variations to address a range of important societal needs. Subsequent work by the marine carbon community and others in the ocean science and operational communities led to an agreed international plan described in the Global Climate Observing System (GCOS) Implementation Plan (GCOS-92, 2004). This foundation observing system was designed to meet climate requirements, but also supports weather prediction, global and coastal ocean prediction, marine hazard warning systems, transportation, marine environment and ecosystem monitoring, and naval applications. Here, we describe efforts made to reach the goals set out in the international plan. Thanks to these efforts, most of the ice-free ocean above 2000 m is now being observed systematically for the first time, and a global repeat hydrographic survey and selected transport measurements supplement these networks.The system is both integrated and composite. It depends upon in situ and satellite networks that measure the same variable using different sensors. In this way, optimum use is made of all available platforms and sensors to maximize coverage and attain maximum accuracy. Wherever feasible, observations are transmitted in real time or near real time to maximize their utility, from short-term ocean forecasting to estimation of century-long trends. Because our historical knowledge of oceanic variability is limited, we are learning about the sampling requirements and needed accuracies as the system is implemented and exploited. The system will evolve as technology and knowledge improve. The biggest challenge for the greater oceanographic community—including both research and operational components—will be demonstrating impacts and benefits sufficient to justify the funds needed to complete the observing system, as well as to sustain its funding for the long term.